Ecosystem services provided by agroforestry home gardens in Bengkulu, Indonesia: Smallholder utilization, biodiversity conservation, and carbon storage - WIRYONO WIRYONO; PAUL KRISTIANSEN; LISA LOBRY DE BRUYN; SAPRINURDIN SAPRINURDIN; STEFFANIE NURLIANA (Society for Indonesian Biodiversity, 2023)
Abstract. Wiryono, Kristiansen P, Bruyn LLD, Saprinurdin, Nurliana S. 2023. Ecosystem services provided by agroforestry home gardens in Bengkulu, Indonesia: Smallholder utilization, biodiversity conservation, and carbon storage. Biodiversitas 24: 2657-2665. Agroforestry system provides ecosystem services such as conserving biodiversity and providing smallholder farmers with food and other daily needs. It can also generate income for the owners. This study was conducted in 105 home gardens of four villages in Bengkulu Province, Indonesia, to analyze tree species diversity and composition, uses, and potential carbon storage in the agroforestry system of home gardens. Tree data were collected on individual trees from 200 plots (10×10 m). Home garden owners were interviewed on the uses of each tree species. The species richness of trees in each village ranged from 18 to 36, with a total of 57 species (29 introduced and 28 native) for four villages. Most trees (30 species) provided food. The above-ground carbon storage of trees ranged from 29 Mg ha-1to 127 Mg ha-1, with an average of 87 Mg ha-1. This study found that the agroforestry system in home gardens serves some ecosystem services, i.e., providing food, medicines, and other daily needs, conserving plant species and the habitat they provide, and storing carbon. These ecosystem services help villagers build resilience to changing environmental and socio-economic conditions.